ANALISIS PEMILIHAN MODA TRANSPORTASI MAHASISWA FAKULTAS MIPA UNIVERSITAS UDAYANA MENGGUNAKAN RANTAI MARKOV - ADIWIJAYA, WIRYA CHANDRA; PRADNYANDARI, NI PUTU AMAYLIA; NINGSIH, FAUZIAH NURHASNA; SIMATUPANG, MARULI; OCTAVANNY, MADE AYU DWI (E-Jurnal Matematika, 2026)
Student mobility on university campuses often depends on multiple transportation options that may shift over time. This study analyzes the dynamics of transportation mode choices among undergraduate students of the Faculty of Mathematics and Natural Sciences at Udayana University using a discrete-time Markov chain approach. The research aims to identify weekly transition patterns among four transportation modes, namely private vehicles, public transportation, online transportation, and walking, and to estimate their long-term usage probabilities. Primary data were obtained through a structured questionnaire distributed to 114 students selected using proportional simple random sampling. The observed transition frequencies were used to construct a one-step transition matrix, whose stochastic properties were then assessed to ensure ergodicity before computing the steady-state distribution to identify the long-run behavioral tendencies. The results indicate that private vehicles remain the dominant mode of transportation both in the current period and in long-term projections, with a steady-state probability of 77.05 percent, while the other modes contribute relatively small proportions. These findings suggest a strong reliance on private transportation among students and highlight the need for improved mobility planning, strengthened alternative transportation options, and the development of more sustainable mobility strategies within the campus environment.